Iridium(I) Complexes with Anionic N‐Heterocyclic Carbene Ligands as Catalysts for H/D Exchange in Nonpolar Media. Issue 18 (3rd June 2020) - Koneczny, Marvin; Phong Ho, Luong; Nasr, Alexandre; Freytag, Matthias; Jones, Peter G.; Tamm, Matthias
Abstract: A series of neutral iridium(I) complexes of the general type [(WCA−NHC)]IrL(COD)] (COD=1, 5‐cyclooctadiene; L=phosphine, pyridine), bearing anionic N‐heterocyclic carbenes (WCA−NHC) with a weakly coordinating anionic (WCA) borate moiety, were prepared by addition of phosphines and pyridine to [(WCA−NHC)]Ir(COD)], in which the available coordination site is stabilized by intramolecular metal‐arene interaction (π‐face donation). The solvent and substrate scope of the neutral complexes as catalysts for H/D exchange was investigated, revealing their suitability for promoting efficient deuteration in nonpolar solvents such as cyclohexane. Abstract :